Eco-educational culture tourism: Efforts to improve community welfare in Timpik Village - Mu'arifuddin, Mu'arifuddin; Rifandi, Raditya Ahmad; Ifriza, Yahya Nur (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to increase the knowledge and capacity of the Timpik Village community in managing sustainable tourism villages through the application of the eco-educational culture tourism concept. The activities carried out included socialization and training for POKDARWIS and PKK organizations. The results of this activity show an increase in community knowledge and capacity in managing sustainable tourism villages based on eco-educational culture tourism. Thus, Timpik Village has the opportunity to develop into a sustainable tourism destination, which not only attracts visitors but also empowers local communities economically and socially.